Analysis of the Effect of Credit Term and Interest Rate Level on the Growth of Micro, Small, and Medium Enterprises - Aldi Neri Silitonga; Yeni Ariesa; Juli Meliza (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines some of the variables influencing the development of MSMEs in Medan City. The study uses a quantitative model using multiple linear regression on secondary reports for 2019–2023, this research proves that loan terms contribute significantly to MSME development, while interest rates do not. Together, both contribute significantly, with a coefficient of determination of 18.8%, indicating that other factors, such as managerial ability, innovation, and macroeconomic conditions, still account for 81.2%. The results confirm that the longer the loan term, the greater the opportunity for MSMEs to grow through more flexible cash flow and capital management. Meanwhile, MSME-friendly financing policies need to be continuously improved to encourage local economic growth.